To Explore or to Exploit? Opportunities, Dynamic Capabilities, and Performance of Maritime Enterprises in Ghana - Acheampong, G.; Aggrey, O.K.; Hansen, A.S. (Journal of African Business, 2023)
This study investigates how the recognition and exploitation of entrepreneurial opportunities influence small business performance via interactions with firm-level innovation capability and learning orientation. We frame the study within the maritime-sector context and seek to contribute to the understanding of how the interplay between opportunity recognition, exploitation, innovation capability and learning orientation affects the entrepreneurial performance of local businesses when there is a technological policy change. The study further frames its arguments from a dynamic capability perspective and tests its arguments with data from 284 local businesses operating in the Port of Tema. Findings reveal that opportunity exploitation and learning orientation as well as their interplay have a positive and significant effect on entrepreneurial performance. The study consequently presents local micro-entrepreneurial reactions to macro-level policy changes within the maritime sector, an issue that has largely remained uninvestigated in the African business literature due to maritime blindness.
Research Article
Keywords: Entrepreneurial opportunities; innovation capability; learning orientation